Analisis Penerimaan Pajak Reklame Terhadap Pendapatan Asli Daerah dan Produk Domestik Regional Bruto di Kota Banjarmasin Tahun 2016-2020 - Kusuma, Nadia; Saipudin, Saipudin (PPJP ULM, 2024)
This study aimed to determine the contribution of advertisement tax, the effectiveness of advertisement tax on local revenue, and the elasticity of advertisement tax on the PDRB of Banjarmasin City in 2016-2020. This study uses a quantitative descriptive research method. It was using secondary data sourced from BPKPAD and the Central Statistic Agency. The results of this study indicate that during the 2016-2020 period, the average contribution of Banjarmasin City advertisement tax revenue to regional income was still low, namely 1.32%. Meanwhile, during the 2016-2020 period, the effectiveness of advertisement tax revenue for the City of Banjarmasin was considered very high with an average of 82.67%. For the 2016-2020 time period, the average advertising tax revenue elasticity for GRDP has an average of -0.28%, so it is inelastic. That is, every 1% change in GRDP, can reduce the realization of advertisement tax by -0.28%.